Experimental research of prototypes of water-foam nozzle - Kamlyuk Андрей; Maksimovich Дмитрий; Chan Дык; Grachulin Александр (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2015)
Developed a prototype water-foam nozzle on the barrel manually combined IBS-50. The description of the developed sample defined methodology for conducting experimental studies. Experimental studies in which determine the effect of the diameter of the nozzle tip and the availability of the grid on the multiplicity of foam obtained at the outlet of the nozzle.